EFFECT OF THE SOUTHEAST ANATOLIA PROJECT GAP TO THE MIGRATION IN ŞANLIURFA - Ayhan Akış; Akif Akkuş (Selçuk Üniversitesi Sosyal Bilimler Enstitüsü Dergisi)
The event of migration has a number of reasons in the filed of the study. The most important of these are finding a job, living better, lack of land priority and blood feud. Until 1990 s, there has been immense migration from Şanlıurfa to the other regions of the country. With the beginning of irrigation from Atatürk Dam in 1995, the population that had migrated out of the city before began to return to the city. With the effect of the irrigation of the dam, migration from the city to the village is important in the city. Besides, “compulsory migration”, which is seen as some settelments in the valley of dam lake moving to other new settelments, is important, too